Secondary battery and electric device
Patent Information
- Application Number
- CN202380044960.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-31
- Publication Date
- 2025-01-10
AI Technical Summary
Existing secondary batteries have a large volume expansion rate during charging and discharging, resulting in poor cycle performance. Repeated regeneration of the solid electrolyte interface film increases the internal resistance of the battery and reduces the dynamic performance.
A silicon-carbon composite material with a three-dimensional network cross-linked pore structure is used as the negative electrode material, and a carboxylate compound is added to the electrolyte to reduce the interface impedance and improve the ion transmission efficiency.
It significantly improves the battery's cycle capacity retention rate and high-rate charge and discharge performance, reduces battery internal resistance, and improves energy density and dynamic performance.
Smart Images

Figure CN119301768A_ABST
Abstract
Description
Secondary batteries and electrical devices Technical Field
[0001] The present application relates to the technical field of secondary batteries, and in particular to a secondary battery and an electrical device. Background Art
[0002] In recent years, secondary batteries have been widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, as well as in power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields.
[0003] Electrode active materials with high gram capacity often have poor cycling and kinetic properties. How to improve the battery energy density while taking into account excellent cycling and kinetic properties through the mutual coordination of the various components of the battery is a technical problem that needs to be solved urgently in this field.
[0004] Summary of the Invention
[0005] This application is made in view of the above-mentioned problems, and its purpose is to provide a secondary battery. By matching the electrolyte and the negative electrode material, the internal resistance of the battery is reduced, and the cycle capacity retention rate and the charge and discharge performance at high rates of the battery are improved.
[0006] A first aspect of the present application provides a secondary battery comprising: a negative electrode plate and an electrolyte; the negative electrode plate comprises a silicon-carbon composite material having a three-dimensional network cross-linked pore structure, and the electrolyte comprises a carboxylate compound.
[0007] The silicon-carbon composite material with a three-dimensional network cross-linked pore structure has a stable porous skeleton and good mechanical strength. It can effectively reduce the volume change of silicon before and after charge and discharge while loading a high silicon content. At the same time, the carboxylate compound used in the electrolyte has a low viscosity and easily enters the three-dimensional cross-linked pore structure of the silicon-carbon composite material, promoting ion transport at the active material / electrolyte interface, effectively reducing interfacial impedance, and improving the battery's cycle performance and high-rate charge and discharge capabilities.
[0008] In any embodiment, the pore volume of the silicon-carbon composite material is Vm cm 3 / g, and Vm is defined by the following formula: Among them, ρ 真 represents the true density of the silicon-carbon composite material, α represents the porosity of the silicon-carbon composite material; based on the total mass of the electrolyte, the mass proportion of the carboxylate compound is EL g / g, EL:Vm is 0.1~11, and can be optionally 1~8.
[0009] When the ratio EL:Vm between the pore volume Vm of the silicon-carbon composite material and the mass proportion EL of the carboxylic acid ester compound in the electrolyte meets the above range, the battery's cycle capacity retention rate and battery rate performance can be improved through the mutual cooperation between the carboxylic acid ester compound and the pores of the silicon-carbon composite material.
[0010] When the ratio EL:Vm between the pore volume Vm of the silicon-carbon composite material and the mass proportion EL of the carboxylate compound in the electrolyte is 1 to 8, the battery's recharge performance is significantly improved while achieving a high cycle capacity retention rate.
[0011] In any embodiment, the porosity α of the silicon-carbon composite material is 2 to 30%, and can be optionally 5 to 20%.
[0012] When the pores of the silicon-carbon composite material meet the above range, it can not only ensure its mechanical strength, but also ensure the silicon loading capacity, and can also improve the battery cycle performance and kinetic performance through effective coordination with the sulfate compounds in the electrolyte.
[0013] In any embodiment, the true density ρtrue of the silicon-carbon composite material is 1.7 to 2.5; optionally 1.9 to 2.3.
[0014] When the true density of the silicon-carbon composite material satisfies the above range, the negative electrode can have a higher loading capacity, thereby increasing the energy density of the secondary battery.
[0015] In any embodiment, based on the total mass of the electrolyte, the mass ratio of the carboxylate compound is EL g / g, the specific surface area of the silicon-carbon composite material is SSA, and EL:SSA is 0.002-0.3, and can be optionally 0.02-0.16 or 0.05-0.12.
[0016] When the ratio EL:SSA between the mass proportion of the carboxylate compound in the electrolyte and the specific surface area SSA of the silicon-carbon composite material meets the above range, the carboxylate compound can be effectively embedded in the pore structure of the silicon-carbon composite material, fully contacting with the silicon-carbon composite material, thereby increasing the migration rate of ions at the electrode / electrolyte interface, reducing the internal resistance of the battery, and improving the cycle performance and high-rate capacity of the battery.
[0017] In any embodiment, the specific surface area SSA of the silicon-carbon composite material is 2 to 10 m 2 / g; 3~7m can be selected 2 / g.
[0018] When the specific surface area SSA of the silicon-carbon composite material meets the above range, the specific surface area of the silicon-carbon composite material is large, the kinetic properties of the material are good, and it is beneficial to improve the first coulombic efficiency of the battery.
[0019] In any embodiment, based on the total mass of the electrolyte, the mass proportion of the carboxylate compound is EL g / g, the total pore volume of the pores with a pore diameter of less than or equal to 100 nm in the silicon-carbon composite material is V1 cm3 / g, EL:V1 is 1 to 110, and can be optionally 10 to 80 cm -3 Or 30~72.
[0020] The carboxylate compound has a smaller molecular volume and can easily enter the small pores of the silicon-carbon composite material, forming a mutual cooperation with the silicon-carbon composite material to further increase the migration rate of ions in the electrode active material, thereby improving the cycle performance and rate performance of the battery.
[0021] In any embodiment, the carboxylate compound is represented by Formula I,
[0022] Wherein, R1 and R2 each independently include at least one of H, halogen-substituted or unsubstituted C1-C6 alkyl.
[0023] In any embodiment, R1 and R2 each independently include at least one of H, methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, n-pentyl, trifluoromethyl, difluoromethyl, trifluoroethyl, 2-fluoropropyl, 2,2-difluoropropyl, and 1,1,1-trifluorobutyl.
[0024] In any embodiment, the conductivity of the electrolyte is 11 to 19 ms / cm, and can be optionally 12 to 16 ms / cm.
[0025] In any embodiment, the viscosity of the electrolyte is 2.5 to 3.7 mPa·s, and can be optionally 3 to 3.5 mPa·s.
[0026] Carboxylate compounds have low viscosity, and their presence in the electrolyte can increase the electrolyte's conductivity, ensuring ion migration within the electrolyte, and improving the battery's cycle and rate performance. When the electrolyte viscosity is between 2.5 and 3.7 mPa·s, it facilitates the wetting of the electrolyte with the positive and negative active materials, increasing the rate of ion migration within the electrolyte and reducing the battery's internal resistance.
[0027] In any embodiment, the carboxylate compound is selected from at least one of methyl formate, methyl acetate, ethyl formate, ethyl acetate, propyl acetate, ethyl propionate, methyl propionate, n-propyl propionate, isopropyl propionate, n-butyl propionate, isobutyl propionate, n-pentyl propionate, isopentyl propionate, ethyl butyrate, n-propyl butyrate, propyl isobutyrate, n-pentyl butyrate, n-pentyl isobutyrate, n-butyl butyrate, isobutyl isobutyrate, n-pentyl valerate, ethyl 2,2-difluoropropionate, propyl 2,2-difluoropropionate, isopropyl 2,2,2-trifluoroacetate, propyl 2,2,2-trifluoroacetate, isopropyl 2,2,2-trifluoroacetate, methyl 2,2,2-trifluoroacetate, and fluoromethyl 2,2,2-trifluoroacetate.
[0028] The above-mentioned carboxylate compounds have small molecular volumes and can effectively enter the three-dimensional network cross-linked pore structure of the silicon-carbon composite material, thereby improving the ion transport kinetics and the charging and discharging capabilities of the battery under high-rate conditions.
[0029] In any embodiment, the silicon-carbon composite material includes: a carbon matrix having a three-dimensional network cross-linked pore structure; and silicon nanoparticles at least partially embedded in the three-dimensional network cross-linked pore structure of the carbon matrix.
[0030] When the silicon-carbon composite material having the above structure is applied to a secondary battery, the cycle performance and energy density of the secondary battery can be improved.
[0031] In any embodiment, the mass ratio of the silicon nanoparticles in the silicon-carbon composite material is greater than or equal to 40%, and can be optionally 40-60%.
[0032] The negative electrode material used in the secondary battery of the present application achieves a high loading amount of silicon nanoparticles in the negative electrode material by adopting a carbon-based material having a three-dimensional network cross-linked pore structure, so that the silicon-carbon composite material has a high capacity and can further improve the energy density of the battery.
[0033] In any embodiment, the silicon nanoparticles include one or more of silicon oxides, amorphous silicon, crystalline silicon, and silicon-carbon composites.
[0034] In any embodiment, the carbon matrix includes one or more of graphite, mesocarbon microbeads, soft carbon, and hard carbon.
[0035] In any embodiment, the powder compaction density of the silicon-carbon composite material after one powder compaction test under a force of 20,000 N is P11 g / cm 3 The compaction density of the silicon-carbon composite material after 20 times of powder compaction under a force of 20000N is P21g / cm 3The ratio satisfies: 1.00<P21 / P11≤1.20, optionally, 1.02≤P21 / P11≤1.10.
[0036] When the ratio of P21 / P11 satisfies the above range, the silicon-carbon composite material has a higher gram capacity and better compressive resistance, thereby improving the structural stability of the negative electrode film layer, so that the secondary battery containing this material has a higher energy density while also having better cycle performance.
[0037] In any embodiment, the powder compaction density of the silicon-carbon composite material after one powder compaction test under a force of 20,000 N is P11 g / cm 3 Satisfies: 1.10≤P11≤1.40, optionally, 1.12≤P11≤1.35.
[0038] The powder compaction density of the silicon-carbon composite material after one powder compaction under a force of 20,000 N is P11 g / cm 3 When the above range is met, the negative electrode film layer has a higher compaction density, so that the secondary battery has a higher energy density.
[0039] In any embodiment, the secondary battery includes at least one of a lithium ion battery, a sodium ion battery, a magnesium ion battery, and a potassium ion battery.
[0040] A second aspect of the present application provides an electrical device comprising the secondary battery of the first aspect. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] FIG1 is a schematic diagram of a secondary battery according to an embodiment of the present application;
[0042] FIG2 is an exploded view of the secondary battery according to one embodiment of the present application shown in FIG1 ;
[0043] FIG3 is a schematic diagram of an electric device using a secondary battery as a power source according to an embodiment of the present application.
[0044] Description of reference numerals:
[0045] 1 secondary battery; 11 housing; 12 electrode assembly; 13 cover plate. DETAILED DESCRIPTION
[0046] Below, the embodiments of the binder, preparation method, electrode, battery, and electrical device of the present application are described in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there may be cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate understanding by those skilled in the art. In addition, the drawings and the following description are provided to enable those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0047] " range " disclosed in the present application is limited in the form of lower limit and upper limit, and given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of special range. The scope limited in this way can be to include end value or not include end value, and can be arbitrarily combined, that is, any lower limit can form a range with any upper limit combination. For example, if the scope of 60-120 and 80-110 is listed for specific parameters, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range value 1 and 2 are listed, and if the maximum range value 3,4 and 5 are listed, then the following range can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In this application, unless otherwise specified, the numerical range " ab " represents the abbreviation of any real number combination between a and b, wherein a and b are all real numbers. For example, a numerical range of "0-5" indicates that all real numbers between "0-5" are listed herein, and "0-5" is simply an abbreviation for these numerical combinations. Furthermore, when a parameter is expressed as an integer ≥ 2, this is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0048] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0049] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0050] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), indicating that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0051] Unless otherwise specified, the terms "include" and "comprising" used in this application may be open-ended or closed-ended. For example, "include" and "comprising" may mean that other components not listed may also be included or that only the listed components are included.
[0052] Unless otherwise specified, the term "or" is used in this application to be inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, the condition "A or B" is satisfied if any of the following conditions hold: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0053] As the application scope of secondary batteries expands, the requirements for secondary battery performance, such as energy density, are gradually increasing. Silicon-based materials have high specific capacity and are suitable negative electrode materials for high-energy-density batteries. However, silicon-based materials have a large volume expansion rate during the charge and discharge process, resulting in poor battery cycle performance. In addition, the solid electrolyte interface film (SEI film) on its surface will repeatedly regenerate as the silicon-based material expands, increasing the internal resistance of the battery and reducing the dynamic performance.
[0054] Based on this, the present application proposes a secondary battery, which includes: a negative electrode plate and an electrolyte, the negative electrode plate includes a silicon-carbon composite material with a three-dimensional network cross-linked pore structure; the electrolyte contains a carboxylate compound.
[0055] In this article, the three-dimensional network cross-linked pore structure generally refers to a structure in which two or more pores are interconnected or interlaced and share pore volume in a silicon-carbon composite material, especially in a pore structure formed by carbon matrix particles.
[0056] The pore structure of the silicon-carbon composite material can be tested using equipment and methods known in the art. For example, it can be tested by using a scanning electron microscope (such as ZEISS Sigma 300). As an example, the following steps can be followed: first, the negative electrode sheet containing the silicon-carbon composite material is cut into a sample to be tested of a certain size (for example, 6 mm × 6 mm), and the sample to be tested is clamped with two conductive and heat-conductive thin sheets (such as copper foil), and the sample to be tested and the thin sheet are glued and fixed with glue (such as double-sided tape), and a flat iron block of a certain mass (such as about 400 g) is used to press for a certain time (such as 1 hour) to make the gap between the sample to be tested and the copper foil as small as possible, and then the edges are trimmed with scissors and glued to a sample table with conductive glue, and the sample is slightly protruding from the edge of the sample table. Then, place the sample stage into the sample holder and lock it securely. Turn on the power of the argon ion cross-section polisher (e.g., IB-19500CP) and evacuate the sample to a vacuum (e.g., 10 Pa to 4 Pa). Set the argon flow rate (e.g., 0.15 MPa), voltage (e.g., 8 kV), and polishing time (e.g., 2 hours). Adjust the sample stage to the rocking mode and start polishing. After polishing, use a scanning electron microscope (e.g., ZEISS Sigma 300) to obtain an ion polished cross-section morphology (CP) image of the sample to be tested.
[0057] The silicon-carbon composite material, with its three-dimensional cross-linked pore structure, possesses a stable porous framework and excellent mechanical strength. It can effectively reduce the volume change of silicon during charge and discharge while simultaneously loading a high silicon content. Furthermore, the low viscosity of the carboxylate compound used in the electrolyte allows for easy integration into the three-dimensional cross-linked pore structure of the silicon-carbon composite material, promoting ion transport at the active material / electrolyte interface, effectively reducing interfacial impedance and improving the battery's cycling performance and high-rate charge and discharge capabilities.
[0058] In some embodiments, the pore volume of the silicon-carbon composite material is Vm cm 3 / g, and Vm is defined by the following formula: Among them, ρ 真 represents the true density of the silicon-carbon composite material, α represents the porosity of the silicon-carbon composite material; based on the total mass of the electrolyte, the mass proportion of the carboxylate compound is EL g / g, and the ratio EL:Vm between the pore volume Vm of the silicon-carbon composite material and the mass proportion EL of the carboxylate compound in the electrolyte is 0.1 to 11, and can be optionally 1 to 8.
[0059] In some embodiments, based on the total mass of the electrolyte, the mass proportion of the carboxylate compound is EL g / g, the pore volume of the silicon-carbon composite material is Vm, and EL:Vm can be selected from 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9, 9.5, 10, 10.5, and 11.
[0060] The pore volume Vm of silicon-carbon composite materials can be calculated using the following formula: Among them, ρ 真 Represents the true density of the silicon-carbon composite material, and α represents the porosity of the silicon-carbon composite material. Porosity refers to the ratio of the pore volume within the particle to the total volume of the carbon matrix particle. Porosity can be measured by the gas replacement method in accordance with GB / T24586. Porosity W = (L1-L2) / L1*100%, where L1 is the apparent volume of the sample and L2 is the true volume of the sample. True density is a well-known meaning in the art, which refers to the actual mass of a solid substance per unit volume when the material is absolutely dense, that is, the density after removing the voids inside the material or the voids between particles; it can be tested using instruments and methods known in the art. For example, the test method can refer to GB / T 24586-2009, and the test instrument can be a true density tester. As an example, the following steps can be followed: place a clean and dry sample cup on a balance, reset the balance to zero, add a certain amount of powder sample into the sample cup (for example, the sample can occupy 1 / 2 of the volume of the sample cup), record the mass of the sample, place the sample cup containing the sample in a true density tester for a closed test, introduce helium, detect the pressure of the gas in the sample chamber and the expansion chamber, and then calculate the true volume and, in turn, the true density according to Bohr's law.
[0061] When the ratio EL:Vm between the pore volume Vm of the silicon-carbon composite material and the mass proportion EL of the carboxylic acid ester compound meets the above range, the added amount of the carboxylic acid ester compound can cooperate with the pore volume Vm of the silicon-carbon composite material to improve the cycle capacity retention rate of the battery and enhance the rate performance of the battery.
[0062] When the ratio EL:Vm between the pore volume Vm of the silicon-carbon composite material and the mass proportion EL of the carboxylic acid ester compound is 1 to 8, the battery's recharge performance is significantly improved while achieving a high cycle capacity retention rate.
[0063] In some embodiments, the porosity α of the silicon-carbon composite material is 2 to 30%, and can be optionally 10 to 20%.
[0064] In some embodiments, the porosity α of the silicon-carbon composite material can be selected to be 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29% or 30%.
[0065] When the pores of the silicon-carbon composite material meet the above range, it can not only ensure its mechanical strength, but also ensure the silicon loading capacity, and can also improve the battery cycle performance and kinetic performance through effective coordination with the sulfate compounds in the electrolyte.
[0066] In some embodiments, the true density of the silicon-carbon composite material is 真 1.7~2.5g / cm 3 ; Optional: 1.9~2.3g / cm 3 .
[0067] In some embodiments, the true density of the silicon-carbon composite material is 真 Available in 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4 or 2.5 g / cm 3 .
[0068] When the true density of the silicon-carbon composite material satisfies the above range, the negative electrode can have a higher loading capacity, thereby increasing the energy density of the secondary battery.
[0069] In some embodiments, based on the total mass of the electrolyte, the mass ratio of the carboxylate compound is EL g / g, the specific surface area of the silicon-carbon composite material is SSA, and EL:SSA is 0.002-0.3, and can be optionally 0.02-0.16 or 0.05-0.12.
[0070] In some embodiments, based on the total mass of the electrolyte, the mass ratio of the carboxylate compound is EL g / g, the specific surface area of the silicon-carbon composite material is SSA, and EL:SSA can be selected from 0.002, 0.003, 0.004, 0.005, 0.006, 0.007, 0.008, 0.009, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.2, 0.21, 0.22, 0.23, 0.24, 0.25 or 0.3.
[0071] In this article, specific surface area SSA is a well-known meaning in the art, usually the surface area is expressed in m 2The unit of % is expressed in g and can be measured using methods and instruments known in the art. For example, it can be measured using an inert gas (e.g., nitrogen) adsorption specific surface area analysis method according to GB / T 19587-2017 and calculated using the BET (Brunauer Emmett Teller) method. The nitrogen adsorption specific surface area analysis can be performed using a Tri-Star 3020 specific surface area pore size analyzer from Micromeritics, USA.
[0072] When the ratio EL:SSA between the mass proportion of the carboxylate compound in the electrolyte and the specific surface area SSA of the silicon-carbon composite material meets the above range, the carboxylate compound can be effectively embedded in the pore structure of the silicon-carbon composite material, fully contacting with the silicon-carbon composite material, thereby increasing the migration rate of ions at the electrode / electrolyte interface, reducing the internal resistance of the battery, and improving the cycle performance and high-rate capacity of the battery.
[0073] In some embodiments, the specific surface area SSA of the silicon-carbon composite material can be selected to be 2 m 2 / g、3m 2 / g、4m 2 / g、5m 2 / g、6m 2 / g、7m 2 / g、8m 2 / g、9m 2 / g or 10m 2 / g, or a range consisting of any two of the above values.
[0074] When the specific surface area SSA of the silicon-carbon composite material meets the above range, the specific surface area of the silicon-carbon composite material is large, the kinetic properties of the material are good, and it is beneficial to improve the first coulombic efficiency of the battery.
[0075] In some embodiments, based on the total mass of the electrolyte, the mass proportion of the carboxylate compound is EL g / g, the total pore volume of pores with a pore diameter of less than or equal to 100 nm in the silicon-carbon composite material is V1 cm3 / g, EL:V1 is 1 to 110, and can be optionally 10 to 80 or 30 to 72.
[0076] The pore volume test method for different pore sizes can refer to GB / T 19587-2004, using the mesopore pore size distribution test BJH (Barret Joyner Halenda), using the gas adsorption and desorption method under the micro-mesopore model and selecting the adsorption branch data to measure and calculate the total pore volume V1 of pores with a pore size of less than or equal to 100 nm.
[0077] In some embodiments, based on the total mass of the electrolyte, the mass proportion of the carboxylate compound is EL g / g, the total pore volume of pores with a pore diameter of less than or equal to 100 nm in the silicon-carbon composite material is V1, and EL:V1 can be selected from 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75, 76, 77, 78, 79, 80, 81, 82, 83, 84, 85, 86, 87, 88, 89, 90, 91, 92, 93, 94, 95, 96, 97, 98, 99, 100, 105 or 110.
[0078] The carboxylate compound has a smaller molecular volume and can easily enter the small pores of the silicon-carbon composite material, forming a mutual cooperation with the silicon-carbon composite material to further increase the migration rate of ions in the electrode active material, thereby improving the cycle performance and rate performance of the battery.
[0079] In some embodiments, the carboxylate compound is represented by Formula I,
[0080] Wherein, R1 and R2 each independently include at least one of H, halogen-substituted or unsubstituted C1-C6 alkyl.
[0081] In some embodiments, R1 and R2 each independently include at least one of H, methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, n-pentyl, trifluoromethyl, difluoromethyl, trifluoroethyl, 2-fluoropropyl, 2,2-difluoropropyl, and 1,1,1-trifluorobutyl.
[0082] In some embodiments, the conductivity of the electrolyte is 11-19 ms / cm, and optionally 12-16 ms / cm.
[0083] In some embodiments, the conductivity of the electrolyte may be 11 ms / cm, 12 ms / cm, 13 ms / cm, 14 ms / cm, 15 ms / cm, 16 ms / cm, 17 ms / cm, 18 ms / cm, or 19 ms / cm.
[0084] In some embodiments, the viscosity of the electrolyte is 2.5 to 3.7 mPa·s, and may be 3 to 3.5 mPa·s.
[0085] In some embodiments, the viscosity of the electrolyte may be 2.5 mPa·s, 2.6 mPa·s, 2.7 mPa·s, 2.8 mPa·s, 2.9 mPa·s, 3.0 mPa·s, 3.1 mPa·s, 3.2 mPa·s, 3.3 mPa·s, 3.4 mPa·s, 3.5 mPa·s, 3.6 mPa·s, or 3.7 mPa·s.
[0086] Carboxylate compounds have low viscosity, and their presence in the electrolyte can increase the electrolyte's conductivity, ensuring ion migration within the electrolyte, and improving the battery's cycle and rate performance. When the electrolyte viscosity is between 2.5 and 3.7 mPa·s, it facilitates the wetting of the electrolyte with the positive and negative active materials, increasing the rate of ion migration within the electrolyte and reducing the battery's internal resistance.
[0087] In some embodiments, the carboxylate compound is selected from at least one of methyl formate, methyl acetate, ethyl formate, ethyl acetate, propyl acetate, ethyl propionate, methyl propionate, n-propyl propionate, isopropyl propionate, n-butyl propionate, isobutyl propionate, n-pentyl propionate, isopentyl propionate, ethyl butyrate, n-propyl butyrate, propyl isobutyrate, n-pentyl butyrate, n-pentyl isobutyrate, n-butyl butyrate, isobutyl isobutyrate, n-pentyl valerate, ethyl 2,2-difluoropropionate, propyl 2,2-difluoropropionate, ethyl 2,2,2-trifluoroacetate, propyl 2,2,2-trifluoroacetate, isopropyl 2,2,2-trifluoroacetate, methyl 2,2,2-trifluoroacetate, and fluoromethyl 2,2,2-trifluoroacetate.
[0088] The above-mentioned carboxylate compounds have small molecular volumes and can effectively enter the three-dimensional network cross-linked pore structure of the silicon-carbon composite material, thereby improving the ion transport kinetics and the charging and discharging capabilities of the battery under high-rate conditions.
[0089] In some embodiments, the silicon-carbon composite material includes: a carbon matrix and silicon nanoparticles, the carbon matrix has a three-dimensional network cross-linked pore structure, and the silicon nanoparticles are at least partially embedded in the three-dimensional network cross-linked pore structure of the carbon matrix.
[0090] The carbon matrix particles of the present application have a stable porous skeleton structure, a strong supporting capacity, a high stress capacity, and excellent mechanical properties and electrical conductivity; the carbon matrix particles include a three-dimensional network cross-linked pore structure, which provides more space for embedding silicon-based nanoparticles, can be used for large-scale silicon storage, and effectively increase the silicon loading capacity in the silicon-carbon composite material. After the carbon matrix particles are compounded with the silicon-based nanoparticles, the electrical conductivity of the silicon-carbon composite material can be improved, while the volume effect of silicon in the process of lithium insertion and extraction can be alleviated, and the stress changes of the silicon-based nanoparticles can be fully withstood, thereby ensuring the structural stability of the silicon-carbon composite material and improving the cycle stability and lithium storage capacity of the silicon-carbon composite material. Therefore, when the silicon-carbon composite material is applied to a secondary battery, the cycle performance and energy density of the secondary battery can be improved.
[0091] In some embodiments, the mass ratio of silicon nanoparticles in the silicon-carbon composite material is greater than or equal to 40%, and can be optionally 40-60%.
[0092] In some embodiments, the mass ratio of silicon nanoparticles in the silicon-carbon composite material may be 40%, 45%, 50%, 55% or 60%.
[0093] The quality of silicon nanoparticles in silicon-carbon composite materials can be tested using methods and equipment known in the art, for example, it can be measured with reference to EPA 6010D-2014 standard; specifically, ICP-OES (elemental analysis-inductively coupled plasma optical emission spectrometry) testing can be used, in which the solid to be tested is first dissolved into a liquid with a strong acid, and then the liquid is introduced into an ICP light source by atomization. The gaseous atoms to be tested are further ionized and excited in a strong magnetic field, and then restored to the ground state from the excited state; in the above process, energy is released and recorded as different characteristic spectral lines for quantitative analysis of trace elements.
[0094] The negative electrode material used in the secondary battery of the present application achieves a high loading amount of silicon nanoparticles in the negative electrode material by adopting a carbon-based material having a three-dimensional network cross-linked pore structure, so that the silicon-carbon composite material has a high capacity and can further improve the energy density of the battery.
[0095] In some embodiments, the silicon nanoparticles include one or more of silicon oxides, amorphous silicon, crystalline silicon, and silicon-carbon composites.
[0096] In some embodiments, the carbon matrix includes one or more of graphite, mesocarbon microbeads, soft carbon, and hard carbon.
[0097] In some embodiments, in the peripheral region of the silicon-carbon composite material, the mass percentage A1 of the carbon element of the silicon-carbon composite material relative to the total mass of the silicon-carbon composite material and the mass percentage B1 of the silicon element of the silicon-carbon composite material relative to the total mass of the silicon-carbon composite material satisfy 0.8≤B1 / A1≤2.5, optionally, 1≤B1 / A1≤1.5, wherein the peripheral region of the silicon-carbon composite material is a region extending from the outer surface of the silicon-carbon composite material to the interior of the silicon-carbon composite material within a distance of r / 2, and r represents the short diameter of the silicon-carbon composite material.
[0098] The silicon content can be determined by inductively coupled plasma (ICP) emission spectroscopy test, as follows: a silicon-carbon composite material is taken as a sample, the sample is digested with aqua regia and hydrofluoric acid HF, and the solution digested for 15 minutes and the completely digested solution are taken for ICP testing. The silicon content in the solution digested for 45 minutes is the silicon content in the "peripheral area of the silicon-carbon composite material."
[0099] The carbon content can be analyzed by infrared absorption carbon-sulfur content analysis according to the GB / T20123-2006 test standard, specifically as follows: take the silicon-carbon composite material as a sample, and the carbon content at 20 minutes of testing is the carbon content of the "peripheral area of the silicon-carbon composite material".
[0100] When A1 and B1 meet the above range, the mass of silicon nanoparticles attached to the inside of the carbon matrix particles is relatively high, which can significantly improve the capacity of the negative electrode active material, and the voltage of metal ion embedding is low, which is conducive to the embedding of metal ions, thereby further improving the rate performance of the secondary battery.
[0101] In some embodiments, the powder compaction density of the silicon-carbon composite material after one powder compaction under a force of 20,000 N is P11 g / cm 3 The compaction density of the silicon-carbon composite material after 20 times of powder compaction under a force of 20,000 N is P21 g / cm 3 The ratio satisfies: 1.00<P21 / P11≤1.20, optionally, 1.02≤P21 / P11≤1.10.
[0102] When the ratio of P21 / P11 satisfies the above range, the silicon-carbon composite material has a higher gram capacity and better compressive resistance, thereby improving the structural stability of the negative electrode film layer, so that the secondary battery containing this material has a higher energy density while also having better cycle performance.
[0103] In some embodiments, the powder compaction density of the silicon-carbon composite material after one powder compaction under a force of 20,000 N is P11 g / cm 3Satisfies: 1.10≤P11≤1.40, optionally, 1.12≤P11≤1.35.
[0104] The powder compaction density of the silicon-carbon composite material after one powder compaction under a force of 20,000 N is P11 g / cm 3 When the above range is met, the negative electrode film layer has a higher compaction density, so that the secondary battery has a higher energy density.
[0105] In some embodiments, a secondary battery includes a negative electrode sheet, wherein the negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material.
[0106] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on either or both of the two opposite surfaces of the negative electrode current collector.
[0107] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer base layer and a metal layer formed on at least one surface of the polymer base material. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy, etc.) on a polymer base material (such as a base material of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0108] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).
[0109] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0110] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).
[0111] In some embodiments, the negative electrode sheet can be prepared by the following method: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components, are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode current collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.
[0112] In some embodiments, a secondary battery includes a positive electrode sheet, which includes a positive electrode collector and a positive electrode film layer disposed on at least one surface of the positive electrode collector, wherein the positive electrode film layer includes the positive electrode active material of the first aspect of the present application.
[0113] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on either or both of the two opposite surfaces of the positive electrode current collector.
[0114] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0115] In some embodiments, the positive electrode active material may adopt the positive electrode active material for batteries that is well known in the art. As an example, the positive electrode active material may include at least one of the following materials: lithium-containing phosphates with an olivine structure, lithium transition metal oxides, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also referred to as NCM 333 ), LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM 523 ), LiNi 0.5 Co0.25 Mn 0.25 O2 (also referred to as NCM 211 ), LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM 622 ), LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM 811 ), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05 O2) and its modified compounds. Examples of olivine-structured lithium-containing phosphates may include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.
[0116] In some embodiments, the positive electrode active material is a nickel-rich material, and the molar ratio of nickel in the transition metal of the positive electrode active material is higher than 85%.
[0117] In some embodiments, the positive electrode film layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), a vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, a vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, a tetrafluoroethylene-hexafluoropropylene copolymer, and a fluorine-containing acrylate resin.
[0118] In some embodiments, the positive electrode film layer may further include a conductive agent. For example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0119] In some embodiments, the positive electrode sheet can be prepared by the following method: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components, are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode current collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0120] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical and mechanical stability can be selected.
[0121] In some embodiments, the material of the separator can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film, without particular limitation. When the separator is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0122] In some embodiments, the secondary battery includes at least one of a lithium ion battery, a sodium ion battery, a magnesium ion battery, and a potassium ion battery.
[0123] In one embodiment of the present application, an electric device is provided, comprising the secondary battery of any embodiment.
[0124] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square, or any other shape. For example, FIG1 shows a secondary battery 1 with a square structure as an example.
[0125] In some embodiments, referring to Figure 2, the outer packaging may include a shell 11 and a cover plate 13. The shell 11 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 11 has an opening connected to the receiving cavity, and the cover plate 13 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can be formed into an electrode assembly 12 through a winding process or a lamination process. The electrode assembly 12 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 12. The number of electrode assemblies 12 contained in the secondary battery 1 can be one or more, and those skilled in the art can select according to specific actual needs.
[0126] An electrical device includes the secondary battery provided in this application. The secondary battery can be used as a power source for the electrical device or as an energy storage unit for the electrical device. Electrical devices may include, but are not limited to, mobile devices (e.g., mobile phones, laptops, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships, satellites, energy storage systems, etc.
[0127] Figure 3 shows an example of an electric device. This device can be a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the high power and high energy density requirements of the secondary battery, a battery pack or battery module can be used.
[0128] Another example device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is generally required to be lightweight and thin, and may use a secondary battery as a power source.
[0129] Example
[0130] Below, the embodiment of the present application is described. The embodiment described below is exemplary and is only used to explain the present application, and is not to be construed as limiting the present application. Where specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. Reagents or instruments used that do not specify the manufacturer are conventional products that can be obtained commercially.
[0131] Primary and secondary batteries
[0132] Example 1
[0133] (1) Preparation of silicon-carbon composite materials
[0134] A gas containing a silicon precursor is provided to carbon matrix particles having a three-dimensional network cross-linked pore structure; silicon nanoparticles attached to the carbon matrix particles are generated from the silicon precursor by chemical vapor deposition to obtain a silicon-carbon composite material. The silicon precursor is silane, and the carbon matrix is hard carbon. The total volume of pores with a pore diameter less than or equal to 100 nm in the carbon matrix particles is recorded as Vc2cm3 / g, and the total volume of pores with a pore diameter greater than 100 nm in the carbon matrix particles is recorded as Vc1cm3 / g, and Vc2 / Vc1 is 10.5. The powder compaction density P11 of the silicon-carbon composite material tested after one powder pressing under a force of 20,000 N is 1.11 g / cm 3 The ratio of the compaction density of the silicon-carbon composite material after 20 times of powder compaction under a force of 20,000 N, P21 to P11, is 1.02.
[0135] (2) Preparation of negative electrode sheet
[0136] The negative electrode active material (silicon-carbon composite), conductive carbon black, thickener sodium carboxymethyl cellulose (CMC), and binder styrene-butadiene rubber latex (SBR) are fully stirred and mixed in an appropriate amount of deionized water at a weight ratio of 96.5:1.0:1.0:1.5 to form a uniform negative electrode slurry; the negative electrode slurry is coated on the negative electrode current collector, and after drying and other processes, a negative electrode sheet is obtained.
[0137] (3) Preparation of positive electrode sheet
[0138] Aluminum foil with a thickness of 8 μm was used as the positive electrode current collector. 0.8 Co 0.1 Mn 0.1 O2(NCM 811 ), the conductive agent acetylene black and the binder polyvinylidene fluoride (PVDF) are dissolved in the solvent N-methylpyrrolidone (NMP) in a weight ratio of 93:2:5, and the mixture is fully stirred to obtain a positive electrode slurry; the positive electrode slurry is then evenly coated on the positive electrode collector, and then dried, cold pressed, and cut to obtain a positive electrode sheet.
[0139] (4) Preparation of electrolyte
[0140] Ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to prepare an organic solvent. Thoroughly dried lithium salt LiPF6 is then dissolved in the mixed organic solvent to prepare an electrolyte solution with a concentration of 1 mol / L. 0.4 wt% ethyl acetate is then added at a specific mass ratio and mixed thoroughly.
[0141] (5) Isolation membrane
[0142] Polypropylene film is used as the isolation film.
[0143] (6) Preparation of batteries
[0144] The positive electrode sheet, separator, and negative electrode sheet are stacked in order, with the separator positioned between the positive and negative electrode sheets to provide isolation. The cells are then wound to obtain a bare cell. The tabs are welded to the bare cell and placed in an aluminum shell. The cells are then baked at 80°C to remove moisture. The electrolyte is then injected and sealed to obtain an uncharged battery. The uncharged battery then undergoes a series of steps, including resting, hot and cold pressing, formation, shaping, and capacity testing, to obtain the lithium-ion battery product of Example 1.
[0145] Example 2-3
[0146] The preparation method of the battery of Example 2-3 is similar to that of Example 1, but the types of additives are adjusted. The specific parameters are shown in Table 1.
[0147] Examples 4-7
[0148] The preparation methods of the batteries of Examples 4-7 are similar to that of Example 1, but the mass proportion of the electrolyte additives in the electrolyte is adjusted. The specific parameters are shown in Table 1.
[0149] Examples 8-11
[0150] The preparation methods of the batteries of Examples 8-11 are similar to those of Example 1, but the pore volume Vm is adjusted by adjusting the porosity α of the silicon-carbon composite material. The pore volume can be calculated by Vm=1 / ρ 真 ×α / (1-α) to calculate.
[0151] Comparative Example 1
[0152] Comparative Example 1 is substantially the same as Example 1, except that no carboxylate compound is added to the electrolyte.
[0153] Comparative Example 2
[0154] The pore structure of the carbon matrix particles in Comparative Example 2 is a honeycomb pore structure. The pores of this structure are not connected, which is not conducive to providing sufficient space for the deposition of silicon, resulting in a relatively low amount of silicon deposition. The mass ratio of silicon particles in the composite material is 7.3%.
[0155] 2. Test Method
[0156] 1. Silicon-carbon composite materials
[0157] 1) Structural characterization of silicon-carbon composites
[0158] The pore structure of the silicon-carbon composite material can be tested using equipment and methods known in the art. For example, it can be tested by using a scanning electron microscope (such as ZEISS Sigma 300). As an example, the following steps can be followed: first, the negative electrode sheet containing the silicon-carbon composite material is cut into a sample to be tested of a certain size (for example, 6 mm × 6 mm), and the sample to be tested is clamped with two conductive and heat-conductive thin sheets (such as copper foil), and the sample to be tested and the thin sheet are glued and fixed with glue (such as double-sided tape), and a flat iron block of a certain mass (such as about 400 g) is used to press for a certain time (such as 1 hour) to make the gap between the sample to be tested and the copper foil as small as possible, and then the edges are trimmed with scissors and glued to a sample table with conductive glue, and the sample is slightly protruding from the edge of the sample table. Then, place the sample stage into the sample holder and lock it securely. Turn on the power of the argon ion cross-section polisher (e.g., IB-19500CP) and evacuate the sample to a vacuum (e.g., 10 Pa to 4 Pa). Set the argon flow rate (e.g., 0.15 MPa), voltage (e.g., 8 kV), and polishing time (e.g., 2 hours). Adjust the sample stage to the rocking mode and start polishing. After polishing, use a scanning electron microscope (e.g., ZEISS Sigma 300) to obtain an ion polished cross-section morphology (CP) image of the sample to be tested.
[0159] 2) Porosity of silicon-carbon composite materials
[0160] After disassembling the battery, the negative electrode film was scraped and then ablated at high temperature to remove the binder to obtain silicon-carbon composite powder. The powder was measured using the gas displacement method according to GB / T 24586. Porosity (P) = (V1 - V2) / V1 * 100%, where V1 is the apparent volume of the sample and V2 is the actual volume.
[0161] 3) Specific surface area SSA of silicon-carbon composite material
[0162] The specific surface area was tested using the gas adsorption method according to the GB / T19587-2017 test standard, as follows: a silicon-carbon composite material was taken as a sample, the sample tube was immersed in liquid nitrogen at -196°C, and the adsorption amount of nitrogen on the solid surface at different pressures was measured at a relative pressure of 0.05-0.30. The monolayer adsorption amount of the sample was obtained based on the BET multilayer adsorption theory and its formula, thereby calculating the specific surface area of the negative electrode active material.
[0163] The BET calculation formula is as follows:
[0164] Where n a —amount of adsorbed gas, in mol / g; p / p0 —relative pressure; nm —monolayer adsorption capacity; C represents a correction parameter, which is used to limit the number of adsorption layers on the adsorbent surface.
[0165] 4) Pore size of silicon-carbon composite material
[0166] The pore size is tested by gas adsorption method according to the test standards GB / T19587-2017 & GB / T21650.2-2008. The specific test method is as follows: a silicon-carbon composite material is taken as a sample, and the sample tube is immersed in liquid nitrogen at -196°C. Nitrogen is adsorbed on the material to be tested at a relative pressure of 0-1. The pore size distribution of the porous material is characterized based on the relationship between the volume of each pore size and the corresponding partial pressure.
[0167] 5) True density of silicon-carbon composite materials
[0168] Referring to GB / T 24586-2009, a true density tester can be used as the testing instrument. For example, the following steps can be followed: Place a clean, dry silicon-carbon composite sample cup on a balance, reset the balance, add a certain amount of powder sample to the cup (for example, the sample can occupy 1 / 2 of the cup's volume), record the mass of the sample, place the sample cup in a true density tester for a sealed test, introduce helium, test the pressure of the gas in the sample chamber and expansion chamber, and then calculate the true volume and, therefore, the true density, based on Bohr's law.
[0169] 6) Mass content of silicon nanoparticles in silicon-carbon composites
[0170] Testing is performed using methods and equipment known in the art, for example, with reference to EPA 6010D-2014 standards. Specifically, ICP-OES (elemental analysis - inductively coupled plasma optical emission spectrometry) testing can be used. The sample to be tested is first dissolved in a strong acid into a liquid, and then the liquid is introduced into an ICP light source by atomization. The gaseous atoms to be tested are further ionized and excited in a strong magnetic field, and then return to the ground state from the excited state. Energy is released in the above process and recorded as different characteristic spectral lines for quantitative analysis of trace elements.
[0171] 2. Electrolyte
[0172] 1) Conductivity test of electrolyte
[0173] The conductivity of the electrolyte was tested using a Shanghai Leici DDSJ-319L conductivity meter. The specific test method is as follows: First, rinse the conductivity cell and electrodes three times with distilled water. Then, rinse the cell and electrodes three times with a small amount of the electrolyte to be tested. Then, pour the electrolyte to be tested into the cell until the liquid level is 1-2 cm above the platinum electrode sheet in the conductivity cell. The cell was then placed in a thermostat set to the test temperature for 15-20 minutes. Set the "Calibrate / Measure" button to the "Measure" position, select the appropriate measurement range, and test the electrolyte conductivity.
[0174] 2) Electrolyte viscosity test
[0175] The viscosity of the electrolyte was tested using a Brookfield cone-plate viscometer. The specific test method is as follows: The sample temperature was controlled using a TC-650 water bath ring system (test temperature was 25°C). Rheocalc T software was used to connect to the host computer for program editing and data acquisition, and to plot the viscosity change curve. A certain amount of electrolyte was placed in a sample cup, which was then fixed to the viscometer. The viscometer host computer and the TC-650 water bath ring system were then connected. The corresponding test program was edited in the Rheocalc T software, and the measurement began after the sample temperature stabilized.
[0176] 3. Battery performance
[0177] 1) Cycle capacity retention rate
[0178] At 25°C, the secondary batteries prepared in each example and comparative example were charged at a constant current rate of 0.5C to a charge cutoff voltage of 4.25V. They were then charged at a constant voltage rate to a current of ≤0.05C, allowed to rest for 5 minutes, and then discharged at a constant current rate of 0.33C to a discharge cutoff voltage of 2V, allowed to rest for 5 minutes. This constituted one charge-discharge cycle. The batteries were subjected to cyclic charge-discharge testing using this method, and the capacity retention of the lithium-ion batteries after 800 cycles was calculated.
[0179] 2) Charge and discharge performance test under high rate conditions
[0180] At 25°C, the secondary batteries prepared in each Example and Comparative Example were charged at a constant current rate of 0.5C to a charge cutoff voltage of 4.25V. They were then charged at a constant voltage rate to a current of ≤0.05C, allowed to stand for 5 minutes, and then discharged at a constant current rate of 0.33C to a discharge cutoff voltage of 2V. The batteries were then charged at a constant current rate of 2C to a charge cutoff voltage of 4.25V, and then discharged at a constant current rate of 0.33C to a discharge cutoff voltage of 2V. Cyclic charge and discharge tests were performed on the batteries using this method, and the capacity retention rate of the lithium-ion batteries after 800 cycles was calculated.
[0181] 3) Battery internal resistance
[0182] At 25°C, the secondary batteries prepared in each embodiment and comparative example and the lithium-ion batteries that had been cycled 800 times at 2C at 25°C were charged to 4.3V at a constant current of 1C. They were then charged at a constant voltage of 4.3V until the current was less than 0.05C, and then discharged at 1C for 30 minutes, adjusting the battery's capacity to 50% SOC. The positive and negative test leads of a TH2523A AC internal resistance tester were then placed in contact with the positive and negative electrodes of the battery, respectively. The internal resistance of the battery was read using the internal resistance tester and recorded as the initial battery internal resistance (mΩ) and the battery internal resistance (mΩ) after 800 cycles, respectively.
[0183] 3. Analysis of test results of various embodiments and comparative examples
[0184] Secondary batteries of various embodiments and comparative examples were prepared according to the above methods, and various parameters were measured. The results are shown in Table 1 below.
[0185] Table 1
[0186] According to the results in Table 1, the negative electrode active material of the batteries of Examples 1-11 is a silicon-carbon composite material with a three-dimensional network cross-linked pore structure, and the electrolyte contains a carboxylate compound. Compared with the battery in Comparative Example 1 in which the negative electrode active material is a silicon-carbon composite material with a three-dimensional network cross-linked pore structure and the electrolyte does not contain a carboxylate compound, and the battery in Comparative Example 2 in which the negative electrode active material is a silicon-carbon composite material with a honeycomb pore structure and the electrolyte contains a carboxylate compound, the batteries of Examples 1-11 exhibit lower internal resistance, higher cycle capacity retention, and better high-rate charge and discharge performance.
[0187] In the comparative example, the negative electrode is a silicon-carbon composite material with a honeycomb pore structure. Silicon particles are not easily deposited inside the honeycomb pore structure. Therefore, the mass content of silicon-based particles in the silicon-carbon composite material with a honeycomb pore structure is low, only 7%, and the silicon element is concentrated on the surface distribution of the composite material. The carbon matrix can hardly play a role in limiting the expansion of silicon-based particles, and the battery's cycle performance is poor.
[0188] From the comparison between Examples 4-5 and 6-7, it can be seen that controlling the ratio EL:Vm between the pore volume Vm of the silicon-carbon composite material and the mass proportion EL of the carboxylic acid ester compound in the electrolyte in the range of 1 to 8 can significantly improve the rate performance of the battery while improving the battery cycle capacity retention rate.
[0189] It can be seen from Examples 8-11 that when the ratio of the mass proportion EL of the carboxylic acid ester compound in the electrolyte to the specific surface area SSA of the silicon-carbon composite material EL:SSA is further controlled to be 0.05-0.12 or EL:V1 is 30-72, the battery exhibits better cycle performance and rate performance.
[0190] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are merely examples, and any embodiments having substantially the same structure and effect as the technical concept within the scope of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the present application, any other embodiments that can be conceived by those skilled in the art and that combine some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A secondary battery, characterized in that: include A negative electrode plate, the negative electrode plate comprising a silicon-carbon composite material having a three-dimensional network cross-linked pore structure; and An electrolyte solution comprising a carboxylic acid ester compound.
2. The secondary battery according to claim 1, characterized in that: The pore volume of the silicon-carbon composite material is Vm cm 3 / g, and Vm is defined by the following formula: Among them, ρ 真 represents the true density of the silicon-carbon composite material, and α represents the porosity of the silicon-carbon composite material; Based on the total mass of the electrolyte, the mass proportion of the carboxylate compound is EL g / g. The ratio EL:Vm between the pore volume Vm of the silicon-carbon composite material and the mass proportion EL of the carboxylate compound in the electrolyte is 0.1-11, and can be 1-8.
3. The secondary battery according to claim 2, characterized in that: The porosity α of the silicon-carbon composite material is 2-30%, and can be optionally 10-20%.
4. The secondary battery according to claim 3 or 4, characterized in that: The true density of the silicon-carbon composite material is 真 1.7~2.5g / cm 3 ; Optional: 1.9~2.3g / cm 3 .
5. The secondary battery according to any one of claims 1 to 4, characterized in that: Based on the total mass of the electrolyte, the mass ratio of the carboxylate compound is EL g / g, the specific surface area of the silicon-carbon composite material is SSA, and EL:SSA is 0.002-0.3, and can be optionally 0.02-0.16 or 0.05-0.
12.
6. The secondary battery according to any one of claims 1 to 5, characterized in that: The specific surface area SSA of the silicon-carbon composite material is 2 to 10 m 2 / g; 3~7m can be selected 2 / g.
7. The secondary battery according to any one of claims 1 to 6, characterized in that: Based on the total mass of the electrolyte, the mass proportion of the carboxylate compound is EL g / g, and the total pore volume of the pores with a pore diameter of less than or equal to 100 nm in the silicon-carbon composite material is V1 cm 3 / g, EL: V1 is 1-110, and can be optionally 10-80 or 30-72.
8. The secondary battery according to any one of claims 1 to 7, characterized in that: The carboxylate compound is represented by formula I, Wherein, R1 and R2 each independently include at least one of H, halogen-substituted or unsubstituted C1-C6 alkyl.
9. The secondary battery according to any one of claims 8, characterized in that: R1 and R2 each independently include at least one of H, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, n-pentyl, trifluoromethyl, difluoromethyl, trifluoroethyl, 2-fluoropropyl, 2,2-difluoropropyl, and 1,1,1-trifluorobutyl.
10. The secondary battery according to any one of claims 1 to 9, characterized in that: The conductivity of the electrolyte is 11-19 ms / cm, and can be optionally 12-16 ms / cm.
11. The secondary battery according to any one of claims 1 to 10, characterized in that: The viscosity of the electrolyte is 2.5 to 3.7 mPa·s, and can be optionally 3 to 3.5 mPa·s.
12. The secondary battery according to any one of claims 1 to 11, characterized in that: The carboxylate compound is selected from at least one of methyl formate, methyl acetate, ethyl formate, ethyl acetate, propyl acetate, ethyl propionate, methyl propionate, n-propyl propionate, isopropyl propionate, n-butyl propionate, isobutyl propionate, n-pentyl propionate, isopentyl propionate, ethyl butyrate, n-propyl butyrate, propyl isobutyrate, n-pentyl butyrate, n-pentyl isobutyrate, n-butyl butyrate, isobutyl isobutyrate, n-pentyl valerate, ethyl 2,2-difluoropropionate, propyl 2,2-difluoropropionate, ethyl 2,2,2-trifluoroacetate, propyl 2,2,2-trifluoroacetate, isopropyl 2,2,2-trifluoroacetate, methyl 2,2,2-trifluoroacetate, and 2,2,2-fluoromethyl trifluoroacetate.
13. The secondary battery according to any one of claims 1 to 12, characterized in that: The silicon-carbon composite material comprises: a carbon matrix having a three-dimensional network cross-linked pore structure; and silicon nanoparticles at least partially embedded in the three-dimensional network cross-linked pore structure of the carbon matrix.
14. The secondary battery according to claim 13, characterized in that: The mass ratio of the silicon nanoparticles in the silicon-carbon composite material is greater than or equal to 40%, and can be optionally 40-60%.
15. The secondary battery according to claim 13 or 14, characterized in that: The silicon nanoparticles include one or more of silicon-oxygen compounds, amorphous silicon, crystalline silicon and silicon-carbon composites.
16. The secondary battery according to any one of claims 13 to 15, characterized in that: The carbon matrix includes one or more of graphite, mesocarbon microbeads, soft carbon and hard carbon.
17. The secondary battery according to any one of claims 1 to 16, characterized in that: The powder compaction density of the silicon-carbon composite material after one powder compaction under a force of 20000N is P11g / cm 3 The compaction density of the silicon-carbon composite material after 20 times of powder compaction under a force of 20000N is P21g / cm 3 The ratio satisfies: 1.00<P21 / P11≤1.20, optionally, 1.02≤P21 / P11≤1.
10.
18. The secondary battery according to any one of claims 1 to 17, characterized in that: The powder compaction density of the silicon-carbon composite material after one powder compaction under a force of 20000N is P11g / cm 3 Satisfies: 1.10≤P11≤1.40, optionally, 1.12≤P11≤1.
35.
19. The secondary battery according to any one of claims 1 to 18, characterized in that: The secondary battery includes at least one of a lithium ion battery, a sodium ion battery, a magnesium ion battery, and a potassium ion battery.
20. An electrical device, characterized in that: A secondary battery comprising the secondary battery according to any one of claims 1 to 19.